Evaluation of Factors influencing the decision to utilizing ICT-based tools in Construction Project and Planning - Pedro, O.; Afolabi, A.O.; Abba, T.; Ajibola, P. (IOP conference series. Materials Science and Engineering, 2021)
Construction planning represents one of the most critical activities in the construction process. This is because it can help predict the failure or success of a construction project. It can also influence the construction project performance in terms of time, cost, and project quality. However, with the advent of information and communication technologies (ICTs) tools in the construction sector, some construction professionals still utilize manual-based tools. Therefore, this study was aimed at evaluating the factors influencing the decision to use ICT based tools in construction planning. The empirical study utilized a questionnaire instrument to sample 70 construction professionals regarding the subject matter. The data collected was analyzed using compare mean scores, principal factor analysis, and categorical regression. The study showed that level of computer literacy, availability of the ICT tool, and performance expectations played an essential role in the decision to utilize ICT-based tools in construction planning. These decision factors were further categorized into Comparative advantage factors, Operational factors, and Individuals/Project factors. The study showed that there were significant factors that can influence the decision to utilized ICT-based tools. These crucial factors include performance expectancy and facilitating conditions. The study recommended the need to increase access to construction planning software and provide necessary ICT infrastructure to facilitate the usage of available ICT-based tools.